Anxiety and depression levels in parents after counselling for fetal heart disease - Erbas, Gizem Seyda; Herrmann-Lingen, Christoph; Ostermayer, Eva; Kovacevic, Alexander; Oberhoffer-Fritz, Renate; Ewert, Peter; Wacker-Gussmann, Annette (Journal of Clinical Medicine, 2023)
The progress in fetal cardiology allows for the early diagnosis of congenital heart defects, but there is still a lack of data on the psychological situation of parents expecting a child with a congenital heart defect. In this cross-sectional study, 77 parents (45 women and 32 men) expecting a child with a heart defect were interviewed with different questionnaires. The standardized Hospital Anxiety and Depression Scale (HADS) questionnaire was used to assess the psychological state of the parents. Various statistical procedures were performed to determine the prevalence, risk factors, and predictors of anxiety and depression. The prevalence for prenatal anxiety was 11.8% and for depressed mood 6.6%, whereas the postnatal prevalence was 25% for anxiety and 16.7% for depressed mood. The mother is influential in protecting against depression as a contact person (p = 0.035). Women were more affected by anxiety and depression than men (p = 0.036). A significant and positive correlation was observed between anxiety and depression before birth (ρ = 0.649, p < 0.001) and after birth (ρ = 0.808, p < 0.001). The level of education correlated negatively with depression (p = 0.016) and anxiety (p = 0.017) before birth. Significantly higher anxiety and depression scores were not observed among health and social workers (p = 0.084), first-time mothers (p = 0.190), and parents whose pregnancies were due to medical assistance (p = 0.051). Close collaboration between maternal-fetal care units, pediatric cardiologists and psychiatric/psychosomatic disciplines is a possible strategy to reduce stress in parents. Therefore, an expert team of professionals, educating with understandable terms and sufficient knowledge about fetal heart disease in parenting counseling, is required. The support of affected parents can positively impact the treatment of the child and should be integrated into the daily routine of the clinic.
Gesehen am 21.11.2023